Classification and competition level effects on push number in wheelchair sport sprinting - Van der Slikke, R.; Berger, M.; Bregman, D.; Lagerberg, A.; Veeger, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Wheelchair sprinting capacity is best measured in a field test, allowing the athlete to freely choose push strategies adapted to their own wheelchair settings, physical ability, classification and speed changes during a sprint. The key test outcome is sprint duration, but there are various push strategies to accomplish the same sprint time. The effect of classification and competition level on the number of pushes needed for a 12m sprint was investigated by field testing 30 male wheelchair basketball athletes in their own wheelchair. International level athletes were expected to be faster with less pushes, and athletes of higher classification (less impaired) were expected to be faster with an unknown possible effect on the number of pushes. Methods: A recently developed method for ambulatory measurement was used to calculate wheelchair kinematics (van der Slikke et al. 2015), providing outcomes on displacement, speed, acceleration and pushes. Additionally maximal isometric push force was recorded and rear seat height was noted. Mutual correlations and competition level differences of sprint characteristics were calculated. Generalized Linear Models (GLM) were drawn to determine the effect of competition level and classification on sprint time and number of pushes. Results: Sprint characteristics did not correlate significantly with classification, only if split by competition level there were significant correlations with sprint time (r=-0.715, p=0.006) and number of pushes (r=-0.647, p= 0.017) in the national level group. Sprint time, number of pushes and isometric push force differed significantly between national and international level wheelchair basketball athletes, with international athletes being faster with fewer pushes. Together, main effects of competition level and classification as factors in GLMs explained 57% of sprint time and 52% of the number of pushes. Discussion: As hypothesized, international level athletes were faster with fewer pushes, even though their higher average seat height was less optimal for propulsion (Mason et al, 2013). The expected relationship between classification and sprint time was clear in the national level athletes, but not present in the internationals. Seat height of lowly classified athletes seemed optimized for sprinting, whereas seat height of highly classified athletes with already adequate sprinting capacity was optimized for upward reach. Although more challenging than well controlled experimental research, the field based setting in this research revealed additional information not only describing the relation between wheelchair setting and performance, but also describing its practical applications if other game demands were taken into account. The results of this approach are believed to assist athletes, coaches and wheelchair experts in decision making concerning wheelchair configuration and athlete training